School Principal Supervision Management In Improving Teacher Pedagogical Competence - Sekar Putri Rahayu Rahmadina; Dinny Mardiana (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research analyzes the implementation of school principal supervision management in improving teacher pedagogical competence at two early childhood education institutions, namely RA Aisyiyah Cimalaka and RA Darussalam. This study aims to fill the research gap by comprehensively examining supervision from a management perspective, using George R. Terry's POAC theory. The importance of the principal's role as a supervisor in maintaining and enhancing teaching quality is often confronted with informal practices and administrative burdens that hinder teacher performance optimization. Employing a qualitative approach with a multiple case study design, data were collected through in-depth interviews, participatory observation, and document studies at both RAs. Research subjects were selected using maximum variation sampling to obtain rich contexts, comparing an organization-affiliated institution with complete facilities and a community-based local institution with limited resources. Data analysis was conducted interactively following the Miles, Huberman, and Saldaña model, encompassing data reduction, data presentation, and conclusion drawing. The research findings indicate that both principals have implemented elements of the POAC theory, albeit with varying levels of formality and effectiveness. In the planning stage, supervision schedules and targets have been prepared, though often informally and not systematically documented. In organizing, RA Aisyiyah Cimalaka involves senior teachers informally, while the principal of RA Darussalam conducts supervision independently. Implementation of supervision at RA Aisyiyah Cimalaka is participatory and reflective, whereas at RA Darussalam it is more incidental and corrective. Evaluation is conducted through routine meetings at RA Aisyiyah Cimalaka and spontaneous feedback at RA Darussalam, though documentation remains a challenge for both. Key supporting factors include harmonious working relationships and teacher commitment, while obstacles are time limitations, the principal's dual roles, and the lack of standardized supervision administration systems. As solutions, RA Aisyiyah Cimalaka focuses on strengthening documentation and collaborative approaches, while RA Darussalam emphasizes supervision discipline, individual coaching, and encouragement for external training. The research concludes that although management principles and professional development have been applied, strengthening administrative systems, structured follow-up of supervision results, and stronger institutional support, in accordance with Permendiknas No. 13 of 2007, are crucial for enhancing supervision effectiveness in developing teacher pedagogical competence.